Hypouricaemic and nephroprotective effects of Poria cocos in hyperuricemic mice by up-regulating ATP-binding cassette super-family G member 2. (1st January 2021) - Liang, Danling; Yong, Tianqiao; Diao, Xue; Chen, Shaodan; Chen, Diling; Xiao, Chun; Zuo, Dan; Xie, Yizhen; Zhou, Xinxin; Hu, Huiping
Abstract: Context: Poria coco F.A.Wolf (Polyporaceae) dispels dampness and promotes diuresis implying hypouricaemic action. Objective: To examine hypouricaemic action of Poria coco . Materials and methods: Ethanol extract (PCE) was prepared by extracting the sclerotium of P. cocos with ethanol, and the water extract (PCW) was produced by bathing the remains with water. PCE and PCW (50, 100 and 200 mg/kg, respectively) were orally administered to hyperuricemic Kunming mice ( n  = 8) to examine its hypouricaemic effect. Also, molecular docking was performed. Results: P. cocos showed excellent hypouricaemic action, decreasing the serum uric acid of hyperuricaemia (HUA) control (526 ± 112 μmol/L) to 178 ± 53, 153 ± 57 and 151 ± 62 μmol/L ( p  < 0.01) by PCE and 69 ± 23, 63 ± 15 and 62 ± 20 μmol/L ( p  < 0.01) by PCW, respectively. According to SCrs, BUNs and H&E staining, PCE and PCW partially attenuated renal dysfunction caused by HUA. They presented no negative effects on ALT, AST and ALP activities. They elevated ABCG2 (ATP-binding cassette super-family G member 2) mRNA and protein expression in comparison to HUA control. In molecular docking, compound 267, 277, 13824, 15730 and 5759 were predicted as the top bioactives of P. cocos against HUA, which even presented better scores than the positive compound, oestrone 3-sulfate. Discussion and conclusions: This paper demonstrated the hypouricaemic and nephroprotective effects of P. cocos in hyperuricemic mice by up-regulating ABCG2. These results may be useful for the development of a hypouricaemic agent.